Why Butterflies Don't Leave. Locational behaviour of entrepreneurial firms - Erik Stam (Max Planck Institute of Economics, 2006)
Entrepreneurship is an important process in regional economic development. Especially the continued growth of a minority of new firms is of major significance to the commercialization of new ideas and employment growth. These growing new firms are transforming on a structural basis, like caterpillars turning into butterflies. However, like butterflies they are at risk to leave their region of origin for better places. This paper analyses how and why the spatial organization of firms develops subsequent to their start-up. A new conceptual framework and an empirical study of the life course of entrepreneurial firms are used to construct a theory on their locational behavior that explains that behavior as the outcome of a process of initiatives taken by entrepreneurs, enabled and constrained by resources, capabilities and relations with stakeholders within and outside of the firm. This study shows that entrepreneurs decide whether or not to move their firm outside of their region of origin for different reasons in distinct phases of the firm life course. Being embedded in social networks, for example, is an important constraint on locational behavior during the early life course of a firm, but over time this becomes less important and other mechanisms like sunk costs increasingly determine the locational behavior of fast-growing firms. The development of the spatial organization is also of major importance: when a multilocational spatial organization has been realized, it is much easier to move the headquarters to another region. The spatial organization of entrepreneurial firms co-evolves with the accumulation of their capabilities. A developmental approach incorporating evolutionary mechanisms and recognizing human agency provides new insights into the age-old study of firm location.
Keywords: D21; L14; L22; M13; R11; R30; 330; location; location behavior; spatial organization; theory of the firm; entrepreneurial firms; entrepreneurship; firm growth; regional economic development; Unternehmer; Betriebliche Standortwahl; Unternehmenswachstum; Theorie der Unternehmung; Regionale Entwicklung